DERADIKALISASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) MODEL KEBERAGAMAAN INKLUSIF DIKALANGAN SISWA SMA - abdurrohman abdurrohman (Universitas Islam Negeri Mataram, Indonesia, 2018)
The phenomenon of religious radicalism has become a global threat of the 21st century that phenomenon was a result of Islam as anaccused religion and was often associated with a terrorist religion. Educational institutions often